Three new species of Paecilaemella (Cosmetidae: Flirteinae) from the upper Amazonian Basin - Medrano, Miguel; Caramori, Laura R.; Kury, Adriano B. (Zootaxa, 2025)
The recent revalidation of Paecilaemella Roewer, 1925 as a valid genus, along with the inclusion of Gonyleptes multimaculatus Wood, 1869, and Protus ornatus Roewer, 1912, in this previously monotypic genus, and its placement in the subfamily Flirteinae, represent significant advances in our understanding of this cosmetid genus and its subfamily. In this study, we further expand our knowledge by describing three new species of Paecilaemella from the Colombian (Paecilaemella andi sp. nov.) and Ecuadorian Amazon forest (Paecilaemella armasi sp. nov. and Paecilaemella geminorum sp. nov.). These three species are distinguishable from its congeners by a striking pattern of spots on the dorsal scutum, resembling the zodiac sign of Gemini. Males of these species share common characteristics, including non-hypertelic chelicerae, an armed distal region of femur IV, extremely elongated basitarsomeres in leg I, and a penis with a basal pair of MS A. Given the limited knowledge of other species in the genus, these characters will require further study to assess whether they represent synapomorphies of the genus.